Now let's have evidence based politics - Jackson, Trevor (BMJ Group, 2003)
Panorama: Fiddling the Figures BBC 1, 29 June at 10 15 pm http://news.bbc.co.uk/1/hi/programmes/panorama/3013062.stm Rating: ★★★